A Curriculum for Blackness: Podcasts as Discursive Cultural Guides, 2010-2020. Issue 2 (2nd July 2020) - Fox, Kim; Dowling, David O.; Miller, Kyle
ABSTRACT: African-American podcasting's ascent marks a potent articulation of Black identity and experience in media history, one reaching an unprecedented range of audiences, dialogs, and online communities. This study examines how content, production practices, and digital audiences for Black podcasting generate a metaphorical curriculum for blackness, a set of discursive cultural guides for listeners. Case studies representative of major genres and publishing sectors where Black podcasting flourished from 2010 to 2020 include humorous commentary on popular entertainment in The Read (2013-), independent media's exploration of Black life in The Nod (2014–2020), and legacy media's in-depth cultural criticism and analysis in Still Processing (2016-).